The Practicality of Student Worksheet in Learning Statistics - Roliza, Eva; Ramadhona, Rezky; Rosmery, Linda (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2018)
The purpose of this study was to develop a practical Student Worksheet on mathematics learning within statistics material. The research method was research and development by using ADDIE namely the analysis stage, planning satge, development stage, and implementation and evaluation stages. This study was limited to the implementation stage which was conducted to look at the practicality of Student Worksheet tested on a limited basis. Based on the test results, practicality of Student Worksheet through three assessment data: the first observation data with an average 71% in a good category, the second data questionnaire responses of teachers with an average 75% in a good category, and the third data questionnaire responses of students with an average 84% in a good category. Keywords: practicalities, Student Worksheet, implementation phase, Creative Statistics